Introduction to Vietnamese law - Mai, Hong Quy (Hong Duc, 2013)
Content: Over view of the Vietnamese state and legal system; Human rights and ensuring business freedoms in Vietnamese; The civil law; Criminal law; Vietnamese law on investment; Law on business Organizations; Commercial law;Labour law; Land law; Tax law...